A REVIEW OF PLANTS USED AGAINST DIABETES MELLITUS BY BAPEDI AND VHAVENDA ETHNIC GROUPS IN THE LIMPOPO PROVINCE, SOUTH AFRICA: USE OF PLANTS AGAINST DIABETES MELLITUS BY BAPEDI AND VHAVENDA - SEMENYA SEBUA SILAS; MAROYI ALFRED (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Traditional utilization of medicinal plants against diabetes mellitus (DM) is common in South Africa and other African countries. This study was aimed at documenting medicinal plants used against DM by the Bapedi and Vhavenda ethnic groups of the Limpopo province, South Africa. This study was based on a review of literature published in scientific journals, books, reports from national, regional, and international organizations, theses and conference papers obtained from libraries and electronic databases. A total of 61 plant species belonging to 39 botanical families, mainly the Fabaceae (n=6), Asteraceae (n=5), and Cucurbitaceae (n=4) were used by Bapedi (n=33) and Vhavenda (n=25) to treat and manage DM. Cassia abbreviata, Momordica balsamina, and Moringa oleifera are used by both the Bapedi and Vhavenda people. Plant parts widely used to prepare DM medicines include roots (40.0%), leaves (27.0%), bark (15.0%), and whole plant (7.0%). Monotherapy preparations made from a single plant species are the most dominant (88.5%) while 11.5% are prepared from a combination of two or more species. More than half (65.5%) of the species used to treat and manage DM are known to possess antidiabetic activities and various secondary metabolites. This study illustrates the importance of medicinal plants in the treatment and management of DM in South Africa.